Gatekeeper identity development: An application of bioecological systems theory. (6th December 2021) - DeCino, Daniel A.; Waalkes, Phillip L.; Chang, Victor
Abstract: Using Bronfenbrenner's bioecological system theory as a framework, we propose an individual's gatekeeper identity development occurs through interactions within multiple social contexts. We conducted a thematic analysis of 11 counselor educators' experiences gatekeeping within each bioecological system. Implications for counselor educators to promote gatekeeper identity development are provided.